A future without forgiveness: beyond reconciliation in transitional justice. Issue 5 (September 2018) - Evans, Matthew
Abstract This article questions the promotion of reconciliation in transitional justice contexts. The article puts forward a critique of reconciliation in practice and questions mainstream definitions of reconciliation. The principle that these forms of reconciliation are desirable is also questioned. It is argued that examples of genuine reconciliation are difficult to find, that the promotion of reconciliation is frequently emphasised at the expense of substantive societal change, that emphasis on reconciliation (narrowly defined) risks taking agency away from those affected by conflict and that emphasis on reconciliation may obscure injustice and may promote acceptance of the status quo. The article suggests that reconciliation is not a necessary condition of, and should be de-emphasised in, transitional justice and, if it is promoted at all, that a different, less prescriptive notion of reconciliation is necessary.